Study of the Process of Processing and Manufacturing Sago Chip Products in the Sagoku Home Industry, Kendari City - Samsul, Andini Wulandari; Herdhiansyah, Dhian; Abdullah, Sukmawati; Asriani, Asriani (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2024)
This research aims to determine the processing and manufacturing process of sago chip products in the Sagoku Home Industry, Kendari City. The research location was determined purposively. Data collection was carried out using observation and documentation methods. The analytical method used is descriptive. The results of the research show that the processing of sago chip products in the Saguku Home Industry begins with the following stages: (1) Providing raw materials, which include 5 kg of sago flour, 5 kg of finely ground corn, 2 kg of moringa leaf flour, 20 tbsp of salt, 15 tsp of pepper, 10 tsp of baking soda, and 15 tsp of baking powder for one production, (2) Mixing process using 1 mixer machine with a maximum capacity of 10 kg, (3) Rolling process with a thickness of 2.5 mm and molded in a circular shape with a diameter of 50 mm, (4) Drying process for 2 days, (5) frying process, (6) Packaging process using mica plastic, with one pack of sago chips weighing 50 grams and a selling price of Rp. 25,000.